Bond Behavior of CRACFST Columns after Exposure to Elevated Temperatures - Peng Hu; Jiong-Feng Liang (Advances in Civil Engineering)
The bond behavior of post-heated circular recycled aggregate concrete-filled steel tube (CRACFST) columns is experimentally investigated in this paper. A total of 24 heated push-out CRACFST specimens are prepared; at the same time, 3 unheated specimens are also prepared and tested for comparison. This paper investigates the effects of five variable parameters, namely, temperature, exposure period, recycled coarse aggregate (RCA) replacement ratio, concrete strength, and interface length-to-diameter ratio, on the bond stress-slip curves and bond strength. The results show that the push-out CRACFST specimens exhibit some differences in bond stress-slip curves at both ambient and high temperature. The bond strength increases with increasing temperature. Other parameters also have influence to some extent. On the basis of a regression analysis of the experimental data, a revised bond strength model is proposed to predict the post-heated bond behavior between recycled aggregate concrete and circular steel tube.